Congenital midline spinal hamartoma in an infant with DICER1 syndrome: A case report - Hammad, Rawan; Lo, Winnie; Chen, Haiying; Shroff, Manohar; Malkin, David; Villani, Anita; Denburg, Avram (Frontiers in Oncology, 2022)
Congenital spinal hamartomas are rare benign tumors. They are mostly seen in infants and are typically asymptomatic at presentation. Spinal hamartomas have not been associated with any known cancer predisposition syndrome. DICER1 syndrome is a well-characterized cancer predisposition syndrome caused by a germline mutation in the DICER1 gene, which shows variable expressivity. To our knowledge, spinal hamartoma has never been described in individuals with DICER1 syndrome. Here, we describe a rare association of congenital spinal hamartoma and DICER1 syndrome in a 5-week-old infant, with molecular findings suggestive of the implication of DICER1 in the pathogenesis of this tumor.